Chorea: Secondary to Non-Ketotic Hyperglycemia: A Case Report - Krishna Sundeep A; Durga Hari Prasad D; Varun P; Lalith Kumar P; Ramakrishna Rao M (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2014)
Chorea associated with non-ketotic hyperglycaemia is an uncommon dyskinetic syndrome in uncontrolled or undiagnosed diabetes. Various theories are postulated but the underlying mechanism remains poorly understood. We report a 70-year-old man suffering from sudden choreodystonic movements and undiagnosed hyperglycemia. It always marks the importance of screening for diabetes as a cause of acute onset of hyperkinetic disorders.